Analisis Kesalahan Penggunaan Simple Past Tense dalam Cerita Pendek oleh Siswa Bahasa Asing - Seruni, Faras (UIN Alauddin Makassar, 2023)
Tenses are a crucial element in the English language. In writing or saying a sentence in English, people should consider what kind of tenses will be used. This study aims to find out what kind of errors are made by eleventh-grade students in writing a short story. The instrument used for the research is the writing test. This qualitative descriptive study involves thirty-one Senior High School students. To know the error made by the students, the researcher used a written test and then analyzed it qualitatively. There are one hundred twenty-eight errors made by the students and it is found seven omission types of error, sixteen errors for addition types, a hundred errors made in misformation, and five errors in misordering. It can be concluded that the students mostly made an error in the misformation type and the students have a low awareness of using verbs in the simple past tense while writing a short story.